INFORMATION CAPABILITIES OF THE TRANSITION FUNCTION OF THE HYDROGEN STORAGE AND SUPPLY SYSTEM GAS GENERATOR TO ASSESS ITS FIRE HAZARD LEVEL - Abramov, Yu.; Kryvtsova, V.; Mykhailiuk, A. (Municipal economy of cities. Series: «Economy science», 2023)
To estimate the level of fire hazard of hydrogen storage and supply systems, it is advisable to use reliability indicators, in particular, of their core element, which is a gas generator. Such indicators include indicators of amplitude and phase reliability of the gas generator, which are determined through the Laplace function. The arguments of this function are the relative errors of the parameters of the gas generator, which are determined by its transition function. Three options for determining the parameters of the gas generator have been developed, the feature of which is obtaining information about its parameters at two a priori given moments. The magnitudes of these moments do not exceed the time of the transient process. In the a priori specified moments, the values of the transient fraction are measured (option 1), and the values of its derivative (option 2) or the value of the integral of the transient function (option 3) are additionally measured. Algorithms for processing the received information have been developed for all options, the implementation of which ensures the determination of gas generator parameters. In terms of its structure, the second option for determining gas generator parameters is the simplest, which has 1.5 times fewer arithmetic operations compared to the first option. In addition, the second option for determining the parameters of the gas generator is invariant to the value of the time parameters that determine the measurement moments. The results of determining the parameters of the gas generator and their nominal values are used to determine the arguments of the Laplace functions. We have specified that when determining the parameters of the gas generator, the complexing method can be used, which involves the implementation of all three information processing algorithms. As an example of the second option of determining gas generator parameters, the structural diagram of the algorithm is presented. We have emphasised that the implementation of the developed algorithms for determining the parameters of the gas generator has no subjective factor associated with the use of expert judgments.